Бренд роботодавця підприємств харчової промисловості - Драган, Олена Іванівна; Соломка, Ольга Миколаївна; Мазник, Ліана Валеріївна (My University, 2022)
У статті досліджуються питання, пов’язані з формуванням бренду роботодавця підприємств харчової промисловості для підтримання ділової репутації та подальшого залучення і розвитку співробітників. Встановлено, що побудова міцного бренду роботодавця є актуальним завданням будь-якого підприємства в умовах посилення конкурентної боротьби за висококваліфікований персонал. Окреслено конкурентні переваги, практики формування і просування бренду роботодавця підприємств харчової промисловості на прикладі компаній Nestle, Roshen, PepsiCo Україна, які вкладають серйозні ресурси у розвиток та підтримку власних HR-брендів.. Виокремлено складові успішного бренду (іміджу) роботодавця для трьох категорій персоналу (студенти та випускники, висококваліфіковані професіонали, інші категорії персоналу). За результатами дослідження визначено, що бренд роботодавця є довгостроковим ресурсом для підприємств харчової промисловості і складним завданням для HR-менеджерів компаній. The questions related to the forming of employer brand of enterprises of food industry for maintenance of business reputation and further engage and development of employees are investigated in the article. Today  it is not enough material motivation for workers, additionally pulled out requirement to the  development, management, certification, prosperity on international standards, participating in projects, and ratings. The construction of strong employer brand is the actual task of any enterprise in the conditions of competitive activity strengthening for highly skilled personnel is set. Key companies that work in the field of employer brand research are distinguished. The modern international and Ukrainian rating of the best employers that measure the companies’ attractiveness from the point of view of employment is analyzed. The major factors of choice by the search of company-employer, in particular stability of company at the market, financial possibility of company, its social responsible position, corporate culture and others are distinguished. Comparison of criteria of choosing employer for youth and for experience specialists is conducted. Competitive edges, practices of forming and advancements of employer brand of enterprises of food industry, are outlined on the example of companies such as Nestle, Roshen, PepsiCo Ukraine, that engage serious resources in development and support of their own HR-brands. At image forming, it is necessary to consider its constituents, as moral values, advertisement sphere, packing material, location and situation in office, personnel dress code, firm’s name, forms of firm, business cards, packages and other is offered in the article. The constituents of successful brand (image) of employer for three categories of personnel (students and graduating students, highly skilled professionals, other categories of personnel) are distinguished. On the results of the research, it is considered that employer brand is a long-term, strategic resource for the enterprises of food industry, and the search of highly skilled specialists is permanent continuous and difficult task for HR-managers of companies.
Keywords: кафедра економіки праці та менеджменту; бренд роботодавця; брендинг; рейтинг; персонал підприємства; компанія; харчова промисловість; employer brand; branding; rating; personnel; enterprises; company; food industry